Multiagent System-Based Adaptive Numerical Relay Design and Development: Part I - Firmware - Shobole, Abdulfetah Abdela; Abafogi, Motuma; Khalid, Hammad; Amireh, Yahia; Zaim, Abdurrahman; Abafogı, Motuma Muktar; Shobole, Abdulfetah Abdela (Kauno Technologijos Universitetas, 2023)
Protection relays that incorporate advanced microprocessors are vital to electrical grids, providing fast and reliable responses to faulty conditions using efficient communication protocols. Instant detection and response to various faults are essential to minimise the risk of damage. Numerical relays can identify faulty conditions and trigger circuit breakers to open, thus preventing further damage to the system. Due to the lack of autonomous decision-making capabilities, existing numerical relays require manual reconfiguration in situations such as a change in network configuration and protection settings. These relays also do not have the ability to coordinate fault clearance when multiple sources supply power to the grid. A comprehensive overview of the research aimed at developing a multiagent system (MAS)-based adaptive protection relay will be provided by dividing it into separate articles such as firmware and hardware. This first part delves into the firmware aspects of this innovative relay, highlighting its adaptive capabilities and key considerations in its development. The second part will provide detailed design descriptions for the hardware features of the relay. An STM32MPU multicore advanced microprocessor is utilised to design and develop the adaptive numerical relay firmware. It incorporates several protection relay ANSI codes, communication protocols, and MAS-based adaptive protection schemes as part of the firmware.
Keywords: Adaptive Protection; IEC 61850; Multiagent System; Power System Protection